Drug-DNA interactions of the mitomycins - Tomasz, Maria (Henry Stewart Talks, 2008)
The mitomycins: structures, properties, early research of the molecular basis of biological activity, Reductive activation, Chemistry of the interactions with DNA: DNA adducts, cross-linking of DNA, Molecular recognition of DNA, Metabolic chemistry, Structure/activity relationships of the DNA adducts